2018
DOI: 10.1214/18-ejs1416
|View full text |Cite
|
Sign up to set email alerts
|

Feasible invertibility conditions and maximum likelihood estimation for observation-driven models

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Following the discussion in Blasques et al (), a sufficient condition for invertibility can be found by generalizing the result in Harvey and Lange (, p. 182). The proposition below is for the Beta‐t‐EGARCH‐M model, to , but with the ARCH‐M score term dropped from .…”
Section: Model Formulationmentioning
confidence: 86%
“…Following the discussion in Blasques et al (), a sufficient condition for invertibility can be found by generalizing the result in Harvey and Lange (, p. 182). The proposition below is for the Beta‐t‐EGARCH‐M model, to , but with the ARCH‐M score term dropped from .…”
Section: Model Formulationmentioning
confidence: 86%
“…Condition A3 ensures thatμ t (•) converges to a stationary and ergodic F t−1 -measurable functionμ t (•) as t → ∞. This is typically referred in the literature as invertibility (Straumann and Mikosch, 2006;Blasques et al, 2018). Condition A4 sets bounds on the updating function.…”
Section: A7mentioning
confidence: 99%
“…Due to the dependence on moving averages that are not available as difference combinations for the first q periods are unavailable, the algorithm requires an initialization ofε t for t ≤ q. As T → ∞, the impact of the initialization on the filter fades exponentially fast almost surely for a stationary process, see for example Blasques et al (2018). For small T however, the impact remains.…”
Section: Penalized Estimationmentioning
confidence: 99%
“…See for exampleBlasques et al (2018) for results on the relation between filters and DGP s. 7 Proofs for Stationarity and Ergodicity of data generated by VARMA models are widespread and can be found for example in(Nsiri and Roy, 1993) Stelzer (2008). treat multivariate Generalized ARMA models including nonidentity links,(Zheng et al, 2015) treat nonlinear theory for Multivariate Markov-switching ARMA processes, finallyAndree et al (2017) show that multivariate ARMA structures can generate geometrically Ergodic data even when a nonlinear observation-driven spatial dependence process is considered.…”
mentioning
confidence: 99%